A comparative analysis of accelerometer and time-motion data in elite men`s hockey training and competition - Polglaze, T.; Dawson, B.; Hiscock, D. J.; Peeling, P. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To determine the relationship between distance covered and player load (PL: sum of accelerations in all 3 planes of movement) in hockey training and competition. Methods: Elite male hockey players (N = 24) wore player-tracking devices in 7 international matches and 7 training sessions. Players were arranged in 4 positional groups (strikers, attacking midfielders, defensive midfielders, defenders) in competition but had generic roles in training. Relationships between distance and PL were assessed in both absolute (m, AU) and relative (m/min, AU/min) terms and were compared between matches and training and between positions within matches, using the Fisher Z test. Results: In competition, the absolute distance-PL relationship was very large overall (r = .868), with no differences between positions. The relative distance-PL relationship was moderate overall (r = .486) and weaker in strikers than in defensive midfielders (Z = 1.785, P = .037) and defenders (Z = 1.690, P = .045). In training, the absolute distance-PL relationship was very large (r = .742), and large (r = .633) in relative terms. The relationship was stronger in competition than training for absolute values (Z = 2.824, P = .005) but not different for relative values. Conclusions: The strong relationship between these variables suggests that PL in hockey is mostly accumulated through running and other locomotor actions, such that PL is not effective in quantifying other activities (evasion, low stance) that contribute to physiological demands, particularly in training.